The role of forensic odontology in the identification of a mutilation victim: A case report - Yatma, Debby; Auerkari, Elza Ibrahim; Yuniastuti, Mindya; Soedarsono, Nurtami; Suhartono, Antonius Winoto; Kaurow, Farah P.; Pasaribu, Roben Suhadi; Auerkari, Pertti (Dental Journal (Majalah Kedokteran Gigi), 2025)
Background: Forensic odontology is an invaluable resource for human identification. An individual’s bones and teeth may be the only remnants of their identity in certain situations where soft tissue has been lost, carbonized, or destroyed for any other reason. The body’s hardest and best-protected structures are found in teeth, and these have individual characteristics and are resistant to factors such as temperature and chemistry. When antemortem dental records are not available for comparison, dental profiling is performed. Purpose: This case study highlights the importance of teeth in the identification process and their usefulness in estimating biological profile factors such as sex, age, and population affinity. Case: The case of an unidentified woman who was found in a house in a severely decomposed, skeletonized state is presented. The unidentified body was sent to the Forensic Medicine Installation of Bhayangkara Level I Hospital to determine the cause of death and for dental identification. Case management: The body was suspected to be a victim of mutilation. Shovel shapes observed on the lingual surface of the lateral upper incisor and tori palatini are the most outstanding diagnostic features in Mongoloid populations. The specific mesiodistal crown width and mandibular canine index revealed female traits. Using the Lamendin method, the age was estimated to be 52–58 years old. Conclusion: A forensic odontologist can identify individuals by comparing antemortem and postmortem dental data. They can also provide age estimation, sex, and population affinity determination by analyzing teeth.